The blockchain-based sharia accounting system: strengthening compliance of islamic rural banks in Indonesia - Nano Suyatna (Institute of Computer Science (IOCS), 2026)
This research discusses the implementation of blockchain technology in Sharia accounting systems to strengthen compliance with Sharia principles, enhance transparency, and strengthen the resilience of institutions at Islamic Rural Banks (BPRS) in Indonesia. The increasing cases of bankruptcy in BPRS due to weak governance and fraudulent practices highlight the need for secure, transparent, and accountable financial infrastructure. Blockchain, with its characteristics of immutability and cryptographic verification, provides a mechanism for recording financial transactions permanently, transparently, and in compliance with Sharia principles, free from elements of riba, gharar, and maysir. This study uses a Hybrid Spiral-Agile approach integrated with the V-Validation model and the Sharia Compliance Loop to develop a blockchain-based accounting system that automates Sharia contracts such as Murabahah, Ijarah, and Mudharabah through smart contracts, enhancing auditability and maintaining data integrity. The research findings indicate that the application of blockchain can speed up the audit process, reduce human errors, and minimize the potential for fraud. Thus, blockchain functions not only as a financial technology innovation but also as a digital trust infrastructure that strengthens ethical governance, transparency, and sustainability in the Sharia finance ecosystem in Indonesia